Pengaruh Alat Peraga Katrol Sederhana terhadap Hasil Belajar Siswa Kelas V Sekolah Dasar - Hendra Budiono; Roma Ulina (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to determine the effect of simple pulley props on the learning outcomes of fifth grade elementary school students. This type of research is experimental research. From the results of the research that has been done by researchers in Science subjects simple plane material using simple pulley props in class V at SDN No.118 / I Ampelu Tuo Village in a homogeneous state. For the influence of the use of simple pulley props on student learning outcomes in simple aircraft material, it can be seen the hypothesis test analysis that there is a positive influence between the use of simple pulley props on the learning outcomes of fifth grade students of SDN No.118 / I Ampelu Tuo Village, Muara Tembesi District. It can be said that the use of simple pulley props has a positive effect on improving the learning outcomes of fifth grade students of SDN No.118 / I Ampelu Tuo Village, Muara Tembesi Sub-district, simple aircraft materials, Science subjects.